Analysis of the Quality of the “Nu-Jek” Website on User Satisfaction Using the Webqual 4.0 Model - Fauziyah, Rahma Sari; Krisbiantoro, Dwi (Journal of Multimedia Trend and Technology, 2025)
Nu-Jek is one of the rapidly growing e-commerce in the online buying and selling market. One of the mobile-based Marketplaces officially entered Indonesia in 2019. Nu-Jek has quite complete features, it can even book buses and hotel reservations. However, there are reports of problems with the missing chat feature, which can affect the quality of interaction. Then about the redesign of the UX and chat features for Nujek noted several usability issues on the main page of the application and the booking section. The study also proposed a new design to fix this problem. The purpose of this study is to analyze the quality of the Nu-Jek website using the Webqual 4.0 method with the variables usability, information quality, service interaction and their effect on user satisfaction both partially and simultaneously. The method used to analyze website quality is the WebQual 4.0 method. The results obtained in this study partially usability has a significant effect on user satisfaction. Information quality partially has a significant effect on user satisfaction. Then partially service interaction has a significant effect on user satisfaction. Simultaneously the variables usability, information quality, service interaction have a significant effect on user satisfaction.